PENGEMBANGAN MEDIA E-LEARNING IPA BERBASIS TEMATIK INTEGRATIF UNTUK MENGEMBANGKAN KEMAMPUAN BERPIKIR KREATIF SISWA - Kiki Pratama Rajagukguk; Nurul Hasanah; Elfi Lailan Syamita Lubis (Jurnal Sintaksis, 2021)
This study aims to determine how the results of developing E-Learning media based on the thematic integrative discovery learning model on the creative thinking abilities of elementary school students in science subjects. The type of research used is Research and Development (R&D) and adapts the Tessmer model. The steps for using the Tessmer model are: self evaluation, expert review and one to one, small group and field test. The trial design used a Quasi Experimental Design in the form of a one-Group pretest posttest design. The data collection instruments in this development consist of validation of material experts, media experts, learning design experts to see the feasibility of the media and student response questionnaires, creative thinking ability test instruments using open ended questions and interviews to see the effectiveness and practicality of the developed e-learning media. The data analysis technique used qualitative data analysis and quantitative data analysis. The results showed that the developed e-learning media was in the category of quite valid and attractive, in the sense that it received an interesting response for students and was very effectively used in the learning process because it could improve students' creative thinking skills.